Relationship of Psychological Variables with Depression A Study on School and College Students - Dhillon, Rupan; Arora, Mehak (JOURNAL OF INDIAN EDUCATION, 2021)
Depression is a mood disorder characterised by a range of symptoms that may include loss of pleasure, feelings of worthlessness and suicidal thoughts, as well as physical states that may affect eating, sleeping, other activities. The current study focuses on perceived stress, coping strategies, hardiness and self-efficacy as the important variables as they relate with depression in adolescents. A sample of 500 adolescents belonging to the age group of 14–17 years is taken for the purpose. Various tests employed in this study are: Beck Depression Inventory (Beck et al., 1996), General Self-efficacy Scale (Schwarzer and Jerusalem,1995), Personal Views Survey (Kobasa, Maddi and Kahn, 1982), Perceived Stress Scale (Cohen et al.,1983) and The Ways of Coping Scale (Folkman and Lazarus,1988). Factor analysis is applied and the results are interpreted on the basis of their factor loadings to understand the significant relationships.